Respostas

2014-06-19T18:22:49-03:00
A(-3;y)  e   B(3;4)    e    D=10
   (x₁;y₁)       (x₂;y₂)

D=√Δx²+Δy²                                  VERIFICANDO:
10=√(x₂-x₁)+(y₂-y₁)                           D=√Δx²+Δy²                          
10=√(3-(-3))+(4-y)                             10=√(3+3)+(4-3)
10=√(3+3)+(4-y)                               10=√9+1
10=√9+4-y                                       (10)²=(√10)²
(10)²=(√9+4-y)²                                 10=10
10=9+4-y
y=9+4-10
y=13-10
y=3
3 5 3